Cooperativity of catalytic and lectin-like domain of Trypanosoma congolense trans-sialidase modulates its catalytic activity. - Mario Waespy; Thaddeus Termulun Gbem; Nilima Dinesh Kumar; Shanmugam Solaiyappan Mani; Jana Rosenau; Frank Dietz; Sørge Kelm (Public Library of Science (PLoS), 2022)
Trans-sialidases (TS) represent a multi-gene family of unusual enzymes, which catalyse the transfer of terminal sialic acids (Sia) from sialoglycoconjugates to terminal galactose or N-acetylgalactosamine residues of oligosaccharides without the requirement of CMP-Neu5Ac, the activated Sia used by typical sialyltransferases. Enzymes comprise a N-terminal catalytic domain (CD) followed by a lectin-like domain (LD). Most work on trypanosomal TS has been done on enzymatic activities focusing on the CD of TS from Trypanosoma cruzi (causing Chagas disease in Latin America), subspecies of Trypanosoma brucei, (causing human sleeping sickness in Africa) and Trypanosoma congolense (causing African Animal Trypanosomosis in livestock). Previously, we demonstrated that T. congolense TS (TconTS)-LD binds to several carbohydrates, such as 1,4-β-mannotriose. In this study we investigated the influence of TconTS3-LD on Sia transfer efficiency of TconTS1a-CD by swapping domains. in silico analysis on structure models of TconTS enzymes revealed the potential of domain swaps between TconTS1a and TconTS3 without structural disruptions of the enzymes overall topologies. Recombinant domain swapped TconTS1a/TS3 showed clear Sia transfer activity, when using fetuin and lactose as Sia donor and acceptor substrates, respectively. While Sia transfer activity remained unchanged from the level of TconTS1a, hydrolytic release of free Neu5Ac as a side product was suppressed resulting in increased transfer efficiency. Presence of 1,4-β-mannotriose during TS reactions modulates enzyme activities enhancing transfer efficiency possibly due to occupation of the binding site in TconTS1a-LD. Interestingly this effect was in the same range as that observed when swapping TconTS1a-CD and TconTS3-LD. In summary, this study demonstrate the proof-of-principle for swapping CDs and LDs of TconTS and that TconTS3-LD influences enzymatic activity of TconTS1a-CD providing evidence that LDs play pivotal roles in modulating activities and biological functions of TconTS and possibly other TS.